Adapting traditional didactic discourse into digital English teaching practices - BURDUJAN, Radu (Acta et Commentationes, Sciences of Education, 2026)
This theoretical–empirical study examines how traditional didactic discourse can be adapted to digital English teaching. It aims to develop principles for designing structured, interactive, and goal-oriented EFL lessons using digital tools. Drawing on discourse analysis, communicative pedagogy, and digital learning theories, the study also analyzes teachers’ perceptions gathered through a structured questionnaire. The data reveal current practices, challenges, and needs in adapting instructional communication to virtual environments. The study ultimately proposes guidelines that preserve pedagogical clarity while leveraging the interactive possibilities of digital platforms.